Synergistic gut microbiome-mediated degradation of Astragalus membranaceus polysaccharides and Codonopsis pilosula polysaccharides into butyric acid: a metatranscriptomic analysis - XinQian Rong; LingFeng Zhu; QingLong Shu (Microbiology Spectrum)
ABSTRACT Astragalus membranaceus and Codonopsis pilosula are traditional Chinese medicines known for their tonifying effects, which are linked to the metabolism of their polysaccharide components in the gut. However, the role of gut microbiota in the degradation of these polysaccharides to butyric acid remains unclear. This study aims to investigate the in vitro degradation of polysaccharides from Astragalus membranaceus and Codonopsis pilosula by healthy mice fecal microbiota, focusing on butyric acid production and the associated microbial gene expression. We conducted an in vitro analysis of the degradation of homogeneous polysaccharides. from Astragalus membranaceus and Codonopsis pilosula using fecal microbiota cultures derived from healthy mice. The fecal microbiota was cultured with the polysaccharides for 48 hours, after which the degradation liquid was collected for butyric acid quantification and metatranscriptome analysis of the microbiota. The degradation of Astragalus membranaceus polysaccharide resulted in a significant increase in butyric acid levels compared to those produced from Codonopsis pilosula polysaccharide or fructooligosaccharide (control). Differential gene expression analysis indicated an upregulation of carbohydrate-active enzymes and genes associated with butyrate production during the degradation of Astragalus membranaceus polysaccharides. Additionally, the findings suggested that synergistic interactions between polysaccharide-degrading and butyrate-producing bacteria play a crucial role in the microbiota’s response to specific polysaccharides. This study highlights the potential of Astragalus polysaccharides to enhance butyric acid production through specific gut microbiota interactions, suggesting their beneficial effects on gut health and metabolism. Further research may provide insights into the therapeutic applications of these traditional medicines in modulating gut microbiota and improving health outcomes.IMPORTANCEThis study significantly advances our understanding of the role of gut microbiota in the metabolism of traditional Chinese medicinal polysaccharides, specifically those from Astragalus membranaceus and Codonopsis pilosula. By demonstrating that Astragalus membranaceus polysaccharide enhances butyric acid production more effectively than Codonopsis pilosula polysaccharide or fructooligosaccharides, the research highlights the potential of these natural compounds in modulating gut health. The identification of upregulated carbohydrate-active enzymes and butyrate production genes provides valuable insights into the microbial mechanisms underlying polysaccharide degradation. This work not only contributes to the field of microbiome research but also supports the development of functional foods and therapeutics aimed at enhancing gut health through targeted polysaccharide consumption.